Validity of Korean Version of Functional Outcomes of Sleep Questionnaire in Patients with Simple Snoring and Obstructive Sleep Apnea - Noh Eul Han; Duck Young Kim; Sang-Ahm Lee (Sleep Medicine Research, 2014)
Background and Objective We developed a Korean version of the Functional Outcomes of Sleep Questionnaire (K-FOSQ) and investigated its reliability and validity in simple snorer or obstructive sleep apnea (OSA) patients. Methods A total 432 participants (70% men, 84% OSA, mean age 50.0 ± 9.8 years) who were simple snorers or had OSA were included. We assessed the internal consistency, test-retest reliability, factor analysis, multitrait scaling analysis, and the concurrent validity of the K-FOSQ. Participants completed a battery of questionnaires including the Epworth Sleepiness Scale (ESS), Short Form-36 Health Survey (SF-36), Medical Outcomes Study-Sleep (MOS-Sleep) Scale, and Beck Depression Inventory (BDI). Results Factor analysis identified five factors, in which only 24 items met the loading criteria. The five factors of K-FOSQ accounted for 73.0% of the variance. Cronbach’s alpha coefficient for all domains exceeded the 0.70 standard for internal consistency. Test-retest reliability was acceptable (r = 0.41–0.93). Item-domain correlations ranged from 0.37 to 0.90. Only one item did not reach the threshold of 0.40. Floor effects were not observed, but ceiling effects were marked on all K-FOSQ subscales except one. All domains of K-FOSQ were significantly correlated with the corresponding scores of all tested instruments. The global K-FOSQ had a strong correlations (r > 0.50) with ESS and Sleep Problem Index-2 of MOS-Sleep, and had medium-sized correlations (r = 0.40–0.50) with BDI and SF-36 total scores. The K-FOSQ global and subscales did discriminate between participants with and without daytime sleepiness, but not between simple snorers and OSA patients. Conclusions The K-FOSQ is a reliable and valid instrument for assessing functional outcome in participants with daytime sleepiness.